Differential expression of matrix metalloproteinase-13 in association with invasion of breast cancer - Kotepui, Manas; Punsawad, Chuchard; Chupeerach, Chaowanee; Songsri, Apiram; Charoenkijkajorn, Lek; Petmitr, Songsak (Contemporary Oncology/Współczesna Onkologia, 2016)
Matrix metalloproteinase-13 (MMP-13) has a potential role in tumour invasion and metastasis. However, its relevance to the prognosis of human breast cancer is poorly understood. The aim of this study is to investigate the expression patterns of MMP-13 protein and to determine its prognostic value in breast cancer, and to define its relation to the clinicopathological features. Immunohistochemistry analysis of MMP-13 was performed on formalin-fixed, paraffin-embedded sections of cancerous breast tissue (n = 76) and normal breast tissue (n = 20), all of which had clinicopathological information available. Based on the principle of immunoreactivity, the detection of MMP-13 on breast tissue was conducted using monoclonal antibodies against MMP-13. A semi-quantitative scoring system was used to assess the presence of, as well as the cellular localisation of MMP-13. MMP-13 expression was significantly greater in the cancerous breast tissues in comparison to those of normal breast tissues. In addition, high levels of MMP-13 expression were also found to be related to the positive detection of breast cancer cells in lymph nodes-amongst breast cancer patients. The results of this study showed that MMP-13 was frequently present in breast tumours, especially when tumours were accompanied by positive breast cancer cell detection in lymph nodes. This suggests that MMP-13 plays a potentially significant role in breast cancer invasion and metastasis.